MANAGEMENT ACCOUNTING AS AN INFORMATION COMPONENT OF THE DIAGNOSTICS OF THE FINANCIAL SECURITY OF ENTERPRISES (World of finance, 2023)
Introduction. New business conditions, characteristic of fundamental changes in the industrial paradigm, the introduction of the digital economy in the socio-economic processes of the "knowledge" information society, the establishment of a new model of world perception and post-war recovery in the conditions of BANI World require a radical change of priorities in the management of financial and economic activities of enterprises in the plane ensuring their safety. The requirements of timeliness and flexibility of management in practical "digital" activities require timeliness of decision-making regarding the functioning of business structures and immediate response to risks and threats in the competitive space. This is provided by the management accounting system, the methodology of which must be constantly reviewed and adapted for implementation in various types of enterprises and organizational and legal formations. The goal is to investigate the main theoretical and methodological approaches to management accounting as an informational component of the financial security of the enterprise.The purpose of the article is the scientific substantiation of the main theoretical and methodological approaches to management accounting as an information component of the financial security of the enterprise.Methods. The study of the outlined problems was achieved with the help of general scientific, special and empirical methods of learning processes and phenomena. Methods of analysis and synthesis, comparison, generalization, applied to the study of management accounting in the context of financial security of the enterprise; scientific abstraction, structural-logical and tabular methods - for the systematization of management accounting technologies in ensuring the financial security of enterprises.Results. The theoretical foundations of management accounting as an information base for managing the financial security of enterprises are summarized. The methodical approaches of management accounting, which allow diagnosing the state of financial and economic activity and making timely management decisions to achieve financial security of enterprises, are highlighted.Conclusions. The informational component of financial security management is management accounting, which produces data of an operational, tactical and strategic nature. The use of analytical methods will expand the volume of information resources about the level of financial security with the necessary level of its detail and frequency of presentation. The use of management accounting methods and technologies makes it possible to generate reliable information for making informed, timely management decisions that can take into account changes in the internal environment and threats and risks of the external environment. The use of analytical methods will expand the volume of information resources about the level of financial security with the necessary level of its detail and frequency of presentation.